Analisa Pengembangan Sistem Pemantau Daya Listrik Berbasis IoT - Fenty Pandansari; Hoedi Prasetyo; Yustina Tri Tularsih (Jurnal Teknik, 2021)
The IoT-based power monitoring device is a device composed of a CT sensor of type SCT-013, an AC-AC power adapter, an Arduino, and a Raspberry Pi. The tool is used to monitor voltage, current, frequency, real power, apparent power and power factor. The measured basic quantities are voltage, current, and frequency. The purpose of the measurement and monitoring processes is to conserve, control the quality, and control the use of electrical energy. In the measurement and monitoring process, tool accuracy is very important because it is closely related to the quality of electrical energy. This study presents an analysis of the accuracy of the power monitoring tool according to the variations in voltage, current, and frequency at the source. The method used is to vary the voltage, current and frequency used as input to the system and compare the measurement results of the power monitor with the Fluke True RMS Multimeter. The test results show that the level of accuracy of the IoT-based power monitoring device on the voltage parameter is 99.1%, the current parameter is 98.75%-99.25% and the frequency is 100%, so it is a proper tool to measure the quality of electrical energy.